Classical Hodgkin Lymphoma of cystic thymus in a patient with infectious mononucleosis: Diagnostic challenges and practical considerations - Nabanita Bhunia; Sarah Ondrejka; Aron Flagg; Ilia N. Buhtoiarov (Elsevier, 2021)
Establishing the diagnosis of classical Hodgkin lymphoma (cHL) in a timely fashion can be a challenge, as there are no pathognomonic signs or symptoms. The percutaneous needle biopsy (CNB) of the tumor gained increased popularity due to its minimal invasiveness and expeditious recovery from procedure. The diagnostic accuracy of CNB depends upon patient size, mass accessibility, and feasibility to obtain diagnostic tissue assuming that the tumor is histologically homogenous. We report on a patient with cHL who underwent multiple CNB from different sites before the diagnosis was established. Yet, only the incisional biopsy of the most metabolically-active tumor site resulted in diagnostic success. It is imperative to thoroughly consider both the biopsy method and the biopsy site for establishing correct diagnosis.